Application of systematic desensitization in a patient with agoraphobia: A single case study - Rahman, Eva; Handoyo, Restu Tri (Psychological Research and Intervention, 2024)
Individuals with agoraphobia disorder tend to be afraid of being in open spaces and have difficulty leaving the house and driving alone. Systematic desensitization is one of the treatments considered effective in treating agoraphobia. The case study aims to determine the application of systematic desensitization in patients with agoraphobia through a single case study design. The participant was a 28-year-old female patient diagnosed with agoraphobia. Systematic desensitization intervention is carried out by following the steps of relaxation exercises, arranging anxiety hierarchies, and gradual exposure to the anxiety sources. The main measurement is carried out through the patient's self-report SUDS (Subjective Units of Discomfort Scale) score for each source of anxiety about open space. The results showed a change in SUDS scores before and after systematic desensitization. Discussion and limitations about this case study are provided for practitioners and researchers interested in systematic desensitization, supported by the explanation of the intervention stages.